The gender gap in populist radical-right voting: examining the demand side in Western and Eastern Europe - Harteveld, Eelco; Van Der Brug, Wouter; Dahlberg, Stefan; Kokkonen, Andrej (Patterns of prejudice, 2015)
In most countries, men are more likely to vote for parties of the populist radical right (PRR) than women. The authors argue here that there are two mechanisms that might potentially explain this gender gap: mediation (women's attitudes and characteristics differ from men's in ways that explain the PRR vote) and moderation (women vote for different reasons than men). They apply these two mechanisms to general theories of support for PRR parties-the socio-structural model, the discontent model, and the policy vote model-and test these on a large sample of voters in seventeen Western and Eastern European countries. The study shows that the gender gap is produced by a combination of moderation and mediation. Socio-structural differences between men and women exist, but the extent to which they explain the gender gap is limited, and primarily restricted to post-Communist countries. Furthermore, women generally do not differ from men in their level of nativism, authoritarianism or discontent with democracy. Among women, however, these attitudes are less strongly related to a radical-right vote. This suggests that men consider the issues of the radical right to be more salient, but also that these parties deter women for reasons other than the content of their political programme. While the existing research has focused almost exclusively on mediation, we show that moderation and mediation contribute almost equally to the gender gap.